Prevention potential of Cordyceps militaris aqueous extract against cyclophosphamind-induced mutagenicity and sperm abnormality in rats - Tongmai, Thanawit; Maketon, Monchan; Chumnanpuen, Pramote (Agriculture and Natural Resources, 2018)
For decades, many natural products (from plants, animals, fungi and bacteria) have been popularly used for nutrapharmaceutical purposes such as treating and preventing a variety of symptoms and diseases. Cordyceps militaris is becoming one of the most popular medicinal mushrooms, especially in Asian countries because of the promising abilities of its extracts in promoting health (antihypertensive, hypoglycemic, sexual potentiative, cancer/tumor prevention, cancer treatment). Nevertheless, research on antimutagenic activity which can protect against DNA damage from chemicals and free radicals is still insufficient. Thus, the present study investigated the antimutagenic effect of aqueous extract from C. militaris in male albino rats using micronucleus and sperm morphology assays. Male Wistar rats (n=15) were orally administered with crude C. militaris extract at doses of 40 mg/kg bodyweight (bw) and 60 mg/kg bw for 3 wk before mutagenic induction using cyclophosphamind (CP). The normal control group received only distilled water (1 mL/d). The results of antimutagenic assay at 1 wk after CP injection showed that the frequency of micronuclei found in the control group after CP injection was higher than for the standard criterion of rat, while, the frequency in the treated group was significantly lower. However, the ratio of polychromatic erythrocytes to normochromatic erythrocytes in all treated groups was lower than that of the standard and the total sperm abnormalities in all treated groups were not significantly different from the control group. These results revealed the potential preventive benefit of a mutagenic effect of C. militaris aqueous extract on male rats.